PENGELOLAAN KEUANGAN PUBLIK DALAM PANDANG MAQASID SYARIAH ISLAM PADA MASA HARUN AR-RASYID - Alimuddin, Agus; Alvia, Risa (AMAL: Jurnal Ekonomi Syariah, 2021)
ABSTRACTIslamic economic perspective, state finances are the top priority to be able to be pooled from the resources gathered and issued for regional development, so as to bring about the welfare of the people. This paper tries to re-examine the management of the public finances during the Abbasid dynasty at the time of Harun Ar-Rasyid's caliph who ruled for 23 years, the state income came from taxes, zakat, and the spoils of war taken in three categories. The purpose of this writing is to find out how the public finances are practiced by the caliph Harun Ar-Rasyid. The method used by library research, Pustaka research aims to collect data and information from the help of various materials contained in the library room, such as books, magazines, documents, records, historical stories and others. To assist in the administration of the state, the caliph formed Diwanul Kharaj to take care of the country's finances. As for the management of financial problems of the State, a financial institution, Baitul Maal (State Treasury) was formed.Keywords: Harun Ar-Rasyid, Islam, Finance. ABSTRAKPerspektif ekonomi Islam, keuangan negara menjadi prioritas utama untuk dapat dikekola dari sumber-sumber yang dihimpun dan dikeluarkan untuk pembangunan wilayah, sehingga dapat mendatangkan kesejahteraan masyarakat. Tulisan ini mencoba menelaah ulang pengelolaan keuangan publik di masa dinasti Abbasiyah pada saat khalifah Harun Ar-Rasyid yang memerintah selama 23 tahun, pendapatan negara berasal dari pajak, zakat, dan rampasan perang yang diambil dengan tiga kategori. Tujuan penulisan ini untuk mengetahui bagaimana keuangan publik yang dipraktikkan oleh khalifah Harun Ar-Rasyid lalu mencoba melihat dengan menggunakan pandangan maqasid syariah. Metode yang digunakan penelitian pustaka, penelitian pustaka bertujuan untuk mengumpulkan data dan informasi dari bantuan bermacam-macam material yang terdapat di ruang perpustakaan, seperti buku-buku, majalah, dokumen, catata, kisah-kisah sejarah dan lain-lainnya. Untuk membantu kegiatan administrasi negara maka khalifah membentuk Diwanul Kharaj untuk mengurus keuangan negara. Sedangkan untuk pengelolaan masalah keuangan Negara maka dibentuk suatu lembaga keuangan yaitu Baitul Maal (Kas Negara).Kata Kunci: Harun Ar-Rasyid, Islam, Keuangan.